Why Does Household Investment Lead Business Investment over the Business Cycle? - Fisher, Jonas D. M. (Journal of Political Economy, 2007)
Household investment leads nonresidential business fixed investment over the U.S. business cycle. Because real business cycle theory has not been able to account for this observation, it represents a potent challenge to the view that transitory productivity disturbances are the main source of aggregate fluctuations. This paper reconciles RBC theory with the investment dynamics by extending the traditional home production model to make household capital complementary to business capital and labor in market production. Empirical evidence suggesting that household capital is a complementary input in market production is also presented.